Understanding Food Policy Councils: Lessons for Extension Partners - Gail Feenstra; Clare Gupta; David Campbell; Jennifer Sowerwine; Katherine Munden-Dixon ([TEST] Journal of Extension, 2021)
This paper presents findings from a survey of 34 food policy councils (FPCs) in California. The survey addressed organizational structure and functions, policy priorities and achievements, and the use of research or other information. We find that most FPCs have formed in recent years, operate with small budgets and limited or no staff, and function primarily to foster network relationships. FPCs rely on community-based knowledge more than academic research, suggesting an opportunity for Extension professionals to lend expertise. We conclude by identifying specific ways Extension professionals can support FPCs as they seek to enhance local and regional food systems.
Keywords: food policy councils; Extension; Policy; Food Systems